HUBUNGAN STATISITIK, PENELITIAN KUANTITATIF DAN SEJARAH PERADABAN ISLAM - Eliyah Eliyah (Prosiding Seminar Nasional Indonesia, 2023)
This research aims to obtain complete and detailed information about the relationship between statistics, quantitative research and the history of Islamic civilization. The method used is a qualitative method, a type of literature review research. The research results show that the Al-Qur'an and Hadith cannot be separated from history. Because the Koran and hadith have recorded a lot of history. Especially the history of Islamic civilization during the time the Prophet Muhammad lived in Mecca and Medina. However, the connection between statistics and the history of Islamic civilization can be seen in the use of statistics itself, especially in war, Islamic law, determining the beginning of the month and many more. Apart from that, the methods used by Islamic scientists are the beginning of research methods based on the principles of positivism, known as quantitative methods. Especially in their discoveries in the form of chemistry, science and many more.